Weighted extropies and past extropy of order statistics and k-record values. Issue 17 (2nd September 2022) - Bansal, Shilpa; Gupta, Nitin
Abstract: In addition to entropy, extropy - the complementary dual of entropy has also gained importance as a measure of information in many areas. Extropy of order statistics, record values and mixed systems, residual extropy properties of k record values, past extropy have been extensively studied in literature. In this paper, we propose length (size) biased shift dependent measures of uncertainty i.e., weighted extropy and weighted residual extropy and study their monotone properties, characterization results, and some other properties in the case of order statistics and k -record values. We also discuss these studies for the past extropy measure.